EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT OF SEWAGE SLUDGE ON SOIL FERTILITY AND THE EFFECT - S. BS., . B oudjabi (university of eloued جامعة الوادي, 2020)
In aims to assess the effect of increasing doses sludge on nutritional quality tIn aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality tIn aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality tIn aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality tIn aims to assess the effect of increasing doses sludge on nutritional quality tIn aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality tIn aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality tIn aims to assess the effect of increasing doses sludge on nutritional quality tIn aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality tIn aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality tIn aims to assess the effect of increasing doses sludge on nutritional quality tIn aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality t In aims to assess the effect of increasing doses sludge on nutritional quality durum wheat wheat wheat and oand o n soil fertility. A soil fertility. A soil fertility. A soil fertility. A soil fertility. A soil fertility. An experiment was n experiment was n experiment was n experiment was n experiment was carried out in a green house carried out in a green house carried out in a green house carried out in a green house carried out in a green house carried out in a green house carried out in a green house carried out in a green house carried out in a green house Faculty of Exact Faculty of Exact Faculty of Exact Faculty of Exact Faculty of Exact Faculty of Exact Faculty of Exact Faculty of Exact Faculty of Exact Faculty of Exact Faculty of Exact Faculty of Exact Faculty of Exact Faculty of Exact Sciences and Natural Life Sciences and Natural Life Sciences and Natural Life Sciences and Natural Life Sciences and Natural Life Sciences and Natural Life Sciences and Natural Life Sciences and Natural Life Sciences and Natural Life Sciences and Natural Life Sciences and Natural Life Sciences and Natural Life Sciences and Natural Life Sciences and Natural Life Sciences and Natural Life Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage Sciences at the University of Tébessa. Four levels sewage sludge (control = 0 g of sludge/ pot; B1 120 sludge (control = 0 g of sludge/pot; B1 120 sludge (control = 0 g of sludge/pot; B1 120 sludge (control = 0 g of sludge/ pot; B1 120 sludge (control = 0 g of sludge/ pot; B1 120 sludge (control = 0 g of sludge/pot; B1 120 sludge (control = 0 g of sludge/pot; B1 120 sludge (control = 0 g of sludge/pot; B1 120 sludge (control = 0 g of sludge/pot; B1 120 sludge (control = 0 g of sludge/ pot; B1 120 sludge (control = 0 g of sludge/ pot; B1 120 sludge (control = 0 g of sludge/pot; B1 120 sludge (control = 0 g of sludge/ pot; B1 120 sludge (control = 0 g of sludge/pot; B1 120 sludge (control = 0 g of sludge/pot; B1 120 sludge (control = 0 g of sludge/ pot; B1 120 sludge (control = 0 g of sludge/pot; B1 120 sludge (control = 0 g of sludge/pot; B1 120 sludge (control = 0 g of sludge/ pot; B1 120 sludge (control = 0 g of sludge/ pot; B1 120 sludge (control = 0 g of sludge/ pot; B1 120 sludge (control = 0 g of sludge/ pot; B1 120 sludge (control = 0 g of sludge/pot; B1 120 sludge (control = 0 g of sludge/pot; B1 120 pot, B2 = 300 g of sl pot, B2 = 300 g of slpot, B2 = 300 g of sl pot, B2 = 300 g of slpot, B2 = 300 g of slpot, B2 = 300 g of sl pot, B2 = 300 g of sl pot, B2 = 300 g of sl pot, B2 = 300 g of sl udge /pot, B3 = dge /pot, B3 = dge /pot, B3 = dge /pot, B3 = dge /pot, B3 = dge /pot, B3 = dge /pot, B3 = dge /pot, B3 = 600 g of sludge of sludge of sludge/pot) were /pot) were /pot) were /pot) were/pot) were brought into plastic pots; brought into plastic pots; brought into plastic pots; brought into plastic pots; brought into plastic pots; brought into plastic pots; brought into plastic pots; each each each each dose is reproduced in three repetitions. is reproduced in three repetitions. is reproduced in three repetitions. is reproduced in three repetitions.is reproduced in three repetitions.is reproduced in three repetitions. is reproduced in three repetitions.is reproduced in three repetitions. is reproduced in three repetitions. is reproduced in three repetitions.is reproduced in three repetitions.is reproduced in three repetitions.is reproduced in three repetitions.is reproduced in three repetitions. is reproduced in three repetitions. is reproduced in three repetitions. is reproduced in three repetitions. The results The results The results The results The results revealed revealed revealedrevealed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed significant increase in the humidity of wheat seed which which amended by amended by amended by amended by amended by the sludge. Plants treated with sludge accumulate the sludge. Plants treated with sludge accumulate the sludge. Plants treated with sludge accumulatethe sludge. Plants treated with sludge accumulate the sludge. Plants treated with sludge accumulatethe sludge. Plants treated with sludge accumulate the sludge. Plants treated with sludge accumulate the sludge. Plants treated with sludge accumulatethe sludge. Plants treated with sludge accumulate the sludge. Plants treated with sludge accumulate the sludge. Plants treated with sludge accumulate the sludge. Plants treated with sludge accumulatethe sludge. Plants treated with sludge accumulatethe sludge. Plants treated with sludge accumulatethe sludge. Plants treated with sludge accumulatethe sludge. Plants treated with sludge accumulatethe sludge. Plants treated with sludge accumulate the sludge. Plants treated with sludge accumulatethe sludge. Plants treated with sludge accumulate more ash, nitrogen more ash, nitrogenmore ash, nitrogenmore ash, nitrogen more ash, nitrogen more ash, nitrogen more ash, nitrogen and fatty acidity compared and fatty acidity compared and fatty acidity compared and fatty acidity compared and fatty acidity compared and fatty acidity compared and fatty acidity compared and fatty acidity compared and fatty acidity compared and fatty acidity compared and fatty acidity compared and fatty acidity compared and fatty acidity compared and fatty acidity compared to control plants. to control plants. to control plants. to control plants. The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase The sewage sludge improves soil fertility; the results have shown an increase in organic m in organic m in organic m in organic m in organic matter, nitrates and phosphorus.atter, nitrates and phosphorus. atter, nitrates and phosphorus.atter, nitrates and phosphorus.atter, nitrates and phosphorus. atter, nitrates and phosphorus. atter, nitrates and phosphorus. atter, nitrates and phosphorus.atter, nitrates and phosphorus.atter, nitrates and phosphorus. atter, nitrates and phosphorus.atter, nitrates and phosphorus. atter, nitrates and phosphorus. In addition,In addition, In addition,In addition, In addition, the electrical conductivity reveals a he electrical conductivity reveals a he electrical conductivity reveals a he electrical conductivity reveals a he electrical conductivity reveals a he electrical conductivity reveals a he electrical conductivity reveals a he electrical conductivity reveals a he electrical conductivity reveals a he electrical conductivity reveals a he electrical conductivity reveals a he electrical conductivity reveals a he electrical conductivity reveals a he electrical conductivity reveals a he electrical conductivity reveals a he electrical conductivity reveals a he electrical conductivity reveals a he electrical conductivity reveals a he electrical conductivity reveals a strong accumulati
artical
Keywords: Seed; ash; Proline; nitrate; Seed; ash; Proline; nitrate; Seed; ash; Proline; nitrate; Seed; ash; Proline; nitrate; Seed; ash; Proline; nitrate; Seed; ash; Proline; nitrate; Seed; ash; Proline; nitrate; Seed; ash; Proline; nitrate; Seed; ash; Proline; nitrate; Seed; ash; Proline; nitrate; starch; organic matter starch; organic matterstarch; organic matter starch; organic matterstarch; organic matterstarch; organic matter starch; organic matter starch; organic matterstarch